2006
DOI: 10.1074/jbc.m602189200
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Importins Function as Nuclear Transport Receptors for the Rev Protein of Human Immunodeficiency Virus Type 1

Abstract: The Rev protein of human immunodeficiency virus type 1 is an RNA-binding protein that is required for nuclear export of unspliced and partially spliced viral mRNAs. Nuclear import of human immunodeficiency virus type 1 Rev has been suggested to depend on the classic nuclear transport receptor importin ␤, but not on the adapter protein importin ␣. We now show that, similar to importin ␣, Rev is able to dissociate RanGTP from recycling importin ␤, a reaction that leads to the formation of a novel import complex.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
93
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(99 citation statements)
references
References 57 publications
3
93
0
3
Order By: Relevance
“…Indeed, even though it is assumed that each epitope can accommodate substantial sequence diversity, the limits are still vague. The fact that some characterized Trn1 cargos lack a PY-NLS suggests that the actual variability is larger than currently conceived (12)(13)(14)(15). We believe that more bimodular NLSs, such as in ADAR1, will be found in the future and that our study will help identifying them.…”
Section: E)mentioning
confidence: 82%
See 1 more Smart Citation
“…Indeed, even though it is assumed that each epitope can accommodate substantial sequence diversity, the limits are still vague. The fact that some characterized Trn1 cargos lack a PY-NLS suggests that the actual variability is larger than currently conceived (12)(13)(14)(15). We believe that more bimodular NLSs, such as in ADAR1, will be found in the future and that our study will help identifying them.…”
Section: E)mentioning
confidence: 82%
“…These principles can be described as follows: a peptide segment of 15-30 residues with intrinsic structural disorder, an overall basic character, and some weakly conserved sequence motifs, including a relatively conserved proline-tyrosine (PY) dipeptide, leading to the name PY-NLS for this class of signals (8). However, many characterized Trn1 cargoes do not contain such a PY-NLS (4,(12)(13)(14)(15). Therefore, Trn1 interacts not only with the well-characterized PY-NLSs, but at least with another class of NLS, the recognition of which is far less understood.…”
mentioning
confidence: 99%
“…Recently, we reported that importin-β, importin-5, importin-7 and transportin function as import receptors for HIV-1 Rev in vitro (Arnold et al, 2006a). In the previous study, we used an excess of import receptors for the import of GST-tagged Rev.…”
Section: Hiv-1 Rev Is Preferentially Imported By Transportin and Impomentioning
confidence: 99%
“…The NLS of HIV-1 Rev is enriched in the basic amino acid arginine and can interact directly with importin-β (Henderson and Percipalle, 1997;Truant and Cullen, 1999). Recently, we demonstrated that additional import receptors, namely importin-5, importin-7 and transportin, bind to the same NLS and mediate the import of HIV-1 Rev in vitro (Arnold et al, 2006a). The identity of the endogenous Rev import receptor, however, remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…We employed a live-cell-based nuclear export system by evaluating the nuclear export capability of Rev, a nucleocytoplasmic shuttling HIV protein with both a basic aminoacid-rich NLS recognized by multiple importins (Arnold et al, 2006) and a classical NES recognized by CRM1 (Askjaer et al, 1998). We used expression vectors derived from Rev-GFP in which the endogenous Rev NES was mutationally inactivated (Henderson and Eleftheriou, 2000).…”
Section: Nitric Oxide Blocks Crm1-dependent Protein Nuclear Exportmentioning
confidence: 99%